Distributed Intelligent Systems A Coordination Perspective - Bedrouni, Abdellah; Mittu, Ranjeev; Boukhtouta, A.; Berger, Jean.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Distributed Intelligent Systems: A Coordination Perspective addresses and comprehensively answers commonly asked questions about coordination in agent-oriented distributed systems. Characterizing the state-of-the-art research in the field of coordination with regard to the development of distributed agent-oriented systems is a particularly complex endeavour, as the space of available approaches is indeed considerable, and research is independently conducted in a great number of domains. While existing books deal with specific aspects of coordination, the major contribution of this book lies in the attempt to provide an in-depth review covering a wide range of issues regarding multi-agent coordination in Distributed Artificial Intelligence. In addition to reporting various sources of confusion, this book outlines the existence of a plethora of strategies and techniques adapted to different problems, agent-oriented systems, environments, and domains. In short, the current book identifies the absence of a single unified approach in addressing multi-agent coordination problems arising in any system or organization. This book, written by world-class leaders in this field, dedicates itself to providing a state-of-the-art review of current coordination strategies and techniques. The book also describes a broad range of application domains which implement many of the coordination strategies and techniques from the field of multi-agent systems. The application domains include defense, transportation, health care, telecommunication and e-business. Based on current practical deployed applications and existing capabilities, this book also identifies and thoroughly examines trends, challenges, and future agent-oriented research directions. Key features: Unveils the lack of coherence and order that characterizes the area of research pertaining to coordination of distributed intelligent systems Examines coordination models, frameworks, strategies and techniques to enable the development of distributed intelligent agent-oriented systems. Provides specific recommendations to realize more widespread deployment of agent-based systems Distributed Intelligent Systems: A Coordination Perspective is designed for a professional audience composed of practitioners and researchers in industry. This book is also suitable as a reference or secondary textbook for advanced-level students in computer science and engineering.
Coordination -- Coordination in Distributed Problem Solving and Planning -- Scalability and Performance Evaluation for the Coordination of Distributed Systems -- Coordination Models and Frameworks -- Coordination Strategies and Techniques -- Learning and Coordination -- Applications of Multi-agent Coordination -- Future Directions and Conclusion.
Keywords: COMPUTER SCIENCE; COMPUTER NETWORK ARCHITECTURES; COMPUTER COMMUNICATION NETWORKS; OPERATING SYSTEMS (COMPUTERS).; INFORMATION SYSTEMS; ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; ARTIFICIAL INTELLIGENCE (INCL. ROBOTICS).; COMPUTER COMMUNICATION NETWORKS; OPERATING SYSTEMS; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS; INFORMATION SYSTEMS AND COMMUNICATION SERVICE